Analisis Bibliometrik Aplikasi Internet of Things (IoT) dalam Pendidikan Vokasi - Sartika Anori; Winda Agustiarmi; M Giatman; Dedy Irfan; Hansi Effendi (Universitas Negeri Padang, 2026)
The rapid integration of Industry 4.0 technologies has necessitated a transformation in vocational education, with the Internet of Things (IoT) emerging as a critical competency. However, a comprehensive mapping of the research landscape in this niche is still limited. This study aims to conduct a bibliometric analysis to identify trends, dominant contributors, and thematic evolutions of IoT applications in vocational education. Data were retrieved from the Scopus database, yielding 121 relevant documents. The analysis focused on four main dimensions: publication year, geographical distribution, subject areas, and source titles, processed through bibliometric mapping techniques. The findings indicate a significant upward trend in publications, reaching its peak in 2024, signaling an urgent global interest in digitalizing vocational training. China and the United States emerged as the most productive countries, reflecting their strategic focus on smart manufacturing and educational innovation. Subject-wise, Engineering and Computer Science dominate the literature, suggesting that research is currently centered on technical infrastructure and system implementation. Furthermore, IEEE was identified as the leading source of publications, reinforcing the technical and standardized nature of current IoT research in the vocational sector. This study highlights a shift from theoretical exploration to practical implementation. The dominance of technical subjects suggests a research gap in the pedagogical and social impacts of IoT, providing a clear direction for future studies to explore the human-centric aspects of IoT-enabled vocational learning.